Projekt tłumaczeniowy „Albatros” - Svirčev, Žarka (Przekłady Literatur Słowiańskich, 2021)
The paper presents the translation concept of the Library Albatross (1921), the most significant project of today’s canonical Serbian modernists and avant-garde writers. This concept is paradigmatic within the modernist creative tendencies and programs between the two world wars. Although Library published only the translation of Poe’s Tales of Mystery and Imagination, the list of announced translations, the paratexts that accompany the Library’s promotional material, and the translation published, allow us to discuss specific translation strategies of Albatross. Albatross translation practice is a template for more comprehensive thinking about poetic innovations of Serbian literature after First World War. Moreover, the Albatross translation platform allows us to consider the concepts of modern/modernism, periphery/center, and world literature in Serbian culture during the twenties.